Invasion of mosquito salivary glands by malaria parasites: prerequisites and defense strategies - Müller, Ann-Kristin; Kohlhepp, Florian; Hammerschmidt-Kamper, Christiane; Michel, Kristin (International journal for parasitology, 2010)
The interplay between vector and pathogen is essential for vector-borne disease transmission. Dissecting the molecular basis of refractoriness of some vectors may pave the way to novel disease control mechanisms. A pathogen often needs to overcome several physical barriers, such as the peritrophic matrix, midgut epithelium and salivary glands. Additionally, the arthropod vector elicites immune responses that can severely limit transmission success. One important step in the transmission of most vector-borne diseases is the entry of the disease agent into the salivary glands of its arthropod vector. The salivary glands of blood-feeding arthropods produce a complex mixture of molecules that facilitate blood feeding by inhibition of the host haemostasis, inflammation and immune reactions. Pathogen entry into salivary glands is a receptor-mediated process, which requires molecules on the surface of the pathogen and salivary gland. In most cases, the nature of these molecules remains unknown. Recent advances in our understanding of malaria parasite entry into mosquito salivary glands strongly suggests that specific carbohydrate molecules on the salivary gland surface function as docking receptors for malaria parasites.
Gesehen am 10.05.2023